Biomethanation of palm oil mill effluent (POME) by ultrasonic-membrane anaerobic system (UMAS) - Sangeethavani, Sundarajan (2017)
Palm oil Mill Effluent (POME) is the wastewater produced during production process of palm oil. POME is a non-toxic thick brownish liquid waste, which has an unpleasant odor. It contains high amounts of total solids, oil and grease, with high concentration of COD and BOD. POME discharged at 80 -90°C and it is fairly acidic with pH ranging from 4.0-5.0. Palm oil mill effluent (POME) with average chemical oxygen demand (COD) and biochemical oxygen demand (BOD) of 70,000 and 30,000 mg/L, respectively, can cause serious environmental hazard if discharged untreated. In this study, methane gas is produced by process of biomethanation of Palm Oil Mill Effluent (POME) using 50L of ultrasonic-membrane Anaerobic System (UMAS). The operating pressure for this study is maintained at 2 bars. Reactor was operated under ambient temperature (30-35 ºC). POME is continuous up-flow feeding from the side flow into the anaerobic reactor. Effluent samples were taken after 5 hours of analysis of COD, pH, alkalinity, suspended solids and volatile suspended solids. Throughout the experiment, the removal efficiency of COD was 95.55% with HRT of 6 days. The BOD removal efficiency was 71.58% while TSS removal rate was from 91 to 99.5%.The methane gas production efficiency was 94.14%. The UMAS treatment efficiency was greatly improved by UMAS introduction. The membrane fouling and polarization at the membrane surface was significantly reduced.